The Girl who Played with Fire (Millennium Trilogy 2) - Stieg Larsson (New York Alfred A. Knopf, 2009)
Mikael Blomkvist, crusading journalist and publisher of the magazine Millennium, has decided to run a story that will expose an extensive sex trafficking operation between Eastern Europe and Sweden, implicating well-known and highly placed members of Swedish society, business, and government.But he has no idea just how explosive the story will be until, on the eve of publication, the two investigating reporters are murdered. And even more shocking for Blomkvist: the fingerprints found on the murder weapon belong to Lisbeth Salander-the troubled, wise-beyond-her-years genius hacker who came to his aid in The Girl with the Dragon Tattoo, and who now becomes the focus and fierce heart of The Girl Who Played with Fire.As Blomkvist, alone in his belief in Salander's innocence, plunges into an investigation of the slayings, Salander herself is drawn into a murderous hunt in which she is the prey, and which compels her to revisit her dark past in an effort to settle with it once and for all.
Keywords: Psychological thriller